Islamic Educational Epistemology in Twentieth-Century Indragiri Hilir: A Philological Study of Majmû‘ al-Âyât wa al-Aḥâdîth - Ridhoul Wahidi; Benny Afwadzi; Nasrullah Nasrullah; Siti Sarah Maidin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines the reconstruction of Islamic education in twentieth-century Indragiri Hilir, Riau, Indonesia through a philological analysis of the manuscript Majmû‘ al-Âyât wa al-Ahâdîth fî Fadâ’il al-‘Ilm by Shaykh Abdurrahman Siddiq al-Banjari. This qualitative study employs philological and intellectual-historical approaches using the manuscript as the primary source and relevant historical literature as supporting data. Content analysis was employed to examine the manuscript’s textual structure and educational themes. The findings indicate that this manuscript represents an effort to develop Islamic education grounded in the Quran and hadith through a systematic and normative approach. The manuscript presents educational principles concerning religious learning, ethics, and scholarly authority. The manuscript integrates 42 Quranic verses, 55 hadith, and classical scholarly authorities, demonstrating the interconnection between epistemic authority, intentionality (niyyah), and transregional knowledge transmission. It also illustrates how Quranic verses and prophetic hadith were pedagogically employed to construct and legitimize educational knowledge within a local scholarly tradition. This study shows that the manuscript contains educational concepts that offer important insights into the development of Islamic education in Indragiri Hilir within its historical context. The manuscript reflects an epistemic framework integrating intellectual, moral, and social dimensions of Islamic education. The findings highlight the value of local manuscripts for reconstructing the history of Islamic education and understanding the epistemological foundations of Islamic learning. Thus, this study contributes to broader discussions in Islamic philology and the history of education in Southeast Asia.